Eating and lifestyle habits associated with regular soft drinks consumption among Brazilian adolescents: National Survey of School Health, 2019 - Carina Castelo Castelucci; Sanda Cristina Oancea; Luciana Bertoldi Nucci (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: To assess the regular consumption of soft drinks among Brazilian adolescents according to sociodemographic characteristics, eating habits, and lifestyle. Methods: This is a cross-sectional study using data from 118,497 adolescents from the 2019 National Survey of School Health (PeNSE), a population survey periodically carried out in Brazil. The prevalence of regular soft drinks consumption was estimated and, using Poisson regression analysis, the association of this consumption with variables related to eating habits and lifestyle (physical and sedentary activities, use of cigarette and alcohol) was verified. Results: The frequency of regular soft drinks consumption was 17.2% (95%CI 16.6–17.8%). Multiple logistic regression analysis showed an association between regular soft drinks consumption and: living in the Southeast and Midwest regions (PR=1.49 and PR=1.50), boys (PR=1.22), eating meals while using a screen on five or more days a week (PR=1.20), eating breakfast less than five days a week (PR=1.14), consuming sweets five or more days a week (PR=2.16), and consuming fast food three or more times a week (PR=2.28). Spending more than three hours a day in sedentary activities (PR=1.18) and cigarette use (PR=1.22) and binge drinking (PR=1.21) were also statistically and significantly associated with regular soft drinks consumption. Conclusion: Adolescents’ regular consumption of soft drinks is associated with the region of residence, sex, and unhealthy eating and lifestyle habits. Interventions to promote the reduction of regular soft drinks consumption among Brazilian adolescents should consider innovative strategies that include comprehensive public policies appropriate to the profile of adolescents.